Telaah Metafisik Ritual Dolop Dalam Masyarakat Dayak Agabag - Satria Satria; Viktorius Siga; Bernardus Subang Hayong; Laurensius Anselmus Wae Woda (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In the effort to explore the true dimensions of life, humans should not focus solely on the empirical and a priori levels. To achieve a deeper understanding, one must free oneself from all forms of attachment to things that are empirical and a priori. Deep reflection is necessary so that the fundamental principles can be discovered, leading to a more essential understanding of reality. This paper aims to analyze the metaphysical dimension contained within the dolop ritual. The findings of this study show that metaphysical reflection can overcome the limited view of reality that is apparent on the surface, which often feels